EDUCATIONAL FAIR USE & DIGITAL LEARNING: COMPARATIVE STUDY BETWEEN INDONESIA & MYANMAR - Mayana, Ranti Fauza; Santika, Tisni; Win, Yin Yin (Faculty of Law, Universitas Pasundan, 2022)
The utilization of copyrighted works for educational purposes under the doctrine of fair use is globally accepted, however, the limit and the implementation measures are not clearly defined. In the age of digital learning where the creation, utilization, and dissemination of information in general and copyrighted works, in particular, have become borderless, it’s critical to analyze the proper implementation of educational fair use. Using juridical normative approach combined with analytical study and comparative study between Indonesia and Myanmar Copyright Law, this research found that both Indonesia and Myanmar Copyright Law provide important exceptions that are specifically aimed at non-commercial educational purposes and public library archival context, however, the implementing regulations of the educational fair use still non-existence. To optimally and effectively implement the doctrine of fair use for educational purposes in the digital age it’s important to adopt globally accepted official guidelines to determine educational fair use more comprehensively followed by synergy, partnership, and collaboration between government, academics, and libraries in formulating both legal and digital infrastructures to guarantee that the implementation of educational fair use in digital age learning complies with national legislation and compliance with international copyright regulations. Keywords: Copyright Law, Digital Learning, Educational Fair Use.